2014
DOI: 10.3402/ejpt.v5.24620
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the co-occurrence of intimate partner violence domains across the life-course: relating typologies to mental health

Abstract: BackgroundThe inter-generational transmission of violence (ITV) hypothesis and polyvictimisation have been studied extensively. The extant evidence suggests that individuals from violent families are at increased risk of subsequent intimate partner violence (IPV) and that a proportion of individuals experience victimisation across multiple rather than single IPV domains. Both ITV and polyvictimisation are shown to increase the risk of psychiatric morbidity, alcohol use, and anger expression.ObjectiveThe curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
58
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 64 publications
9
58
1
Order By: Relevance
“…Seven studies included participants from the United States, one study included participants from Ireland (Armour & Sleath, ), and one study included participants from Australia (McCutcheon et al., ). Most studies had female‐only samples (Cavanaugh, Martins, Petras, & Campbell, ; Cavanaugh et al., ; Golder, Connell, & Sullivan, ; Walsh, Senn, & Carey, ; Young‐Wolff et al., ), or mostly female participants (Armour & Sleath, ; Holt et al., ). One study included only males (Burns, Lagdon, Boyda, & Armour, ), and one study had a relatively balanced gender distribution, and was distinct in that it was conducted with twins (McCutcheon et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven studies included participants from the United States, one study included participants from Ireland (Armour & Sleath, ), and one study included participants from Australia (McCutcheon et al., ). Most studies had female‐only samples (Cavanaugh, Martins, Petras, & Campbell, ; Cavanaugh et al., ; Golder, Connell, & Sullivan, ; Walsh, Senn, & Carey, ; Young‐Wolff et al., ), or mostly female participants (Armour & Sleath, ; Holt et al., ). One study included only males (Burns, Lagdon, Boyda, & Armour, ), and one study had a relatively balanced gender distribution, and was distinct in that it was conducted with twins (McCutcheon et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies found a best‐fitting three‐class solution and four studies found a best‐fitting four‐class solution. Seven studies found a class characterized by a higher likelihood of endorsement of most/all assessed traumas relative to other classes (“ high‐trauma class ”; Armour & Sleath, ; Burns et al., ; Cavanaugh et al., ; Golder et al., ; Holt et al., ; Walsh et al., ; Young‐Wolff et al., ). Further, all studies found a latent class with lower endorsement of most/all assessed traumas relative to other classes (“ low‐trauma class” ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These associations were examined based on research suggesting that individuals who experience and/or enact multiple types of violence may experience more severe mental health consequences than those who are involved in only one type of violence (Finkelhor 2007; Armour and Sleath 2014; Haynie et al 2013; Sabina and Straus 2008). For example, Haynie et al (2013) found that multiform aggressive victims reported higher levels of concurrent depressive symptoms and psychological complaints than did verbal aggressive victims.…”
Section: The Current Studymentioning
confidence: 99%
“…Exposure to IPV in childhood has been shown to increase the likelihood of becoming a perpetrator of IPV, a victim of IPV, or both during early adulthood (Smith et al, 2011). Additionally, children who witness IPV are more likely to have increased instances of psychiatric disorders, alcohol abuse, and issues with anger expression in adulthood (Armour & Sleath, 2014). Similarly, research on Adverse Childhood Experiences (ACE) investigates complex intersections of the effects of poverty, violence, and oppression in childhood on adult health (Cronholm et al, 2015).…”
Section: Lasting Effects Of Interpersonal Violencementioning
confidence: 99%